Public health significance of head and neck cancer - A narrative review - Fatma Ahmed; Sabria Al Marshoudi; Syed Wali Peeran (Wolters Kluwer Medknow Publications, 2020)
Head and neck cancers (HNCs) are a term describing the biologically heterogeneous group of cancers that affect the upper aerodigestive tract and share a common anatomic origin. HNC is one of the most prevalent types of cancers globally. This narrative review is based on a comprehensive search of Medline, Google Scholar, the Cochrane Database of Systematic Reviews, and other electronic databases. The scientific literature in English language dealing with HNCs with relevance to public health significance was reviewed. Various topics of controversy in dealing with the public health significance of HNC have been highlighted in this report in context to the needs of the HNC patients. The search revealed significant gaps in public health delivery for HNC patients. Moreover, conclusively, we recommend that the health-care professionals should be better trained to handle the needs of HNC patients.